Handbook Timing Belts Principles, Calculations, Applications - Perneder, Raimund; Osborne, Ian.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Timing belts offer a broad range of innovative drivetrain solutions; they allow low-backlash operation in robot systems, they are widely used in automated processes and industrial handling involving highly dynamic start-up loads, they are low-maintenance solutions for continuous operation applications, and they can guarantee exact positioning at high operating speeds. Based on his years of professional experience, the author has developed concise guidelines for the dimensioning of timing belt drives and presents proven examples from the fields of power transmission, transport and linear transfer technology. He offers definitive support for dealing with and compensating for adverse operating conditions and belt damage, as well as advice on drive optimization and guidelines for the design of drivetrain details and supporting systems. All market-standard timing belts are listed as brand neutral. Readers will discover an extensive bibliography with information on the various manufacturers and their websites. This practical handbook addresses both the needs of application engineers working in design, development and machine-building, and is well-suited as a textbook for students at universities and vocational schools alike.
1. An Easy Way to the Right Drive -- 2. Principles -- 3. Timing Belts in Drive Technology -- 4. Timing Belts in Linear Motion -- 5 Timing Belts in Transport -- 6 Timing Belt Failure -- 7 Annex.
Keywords: Engineering; Engineering design; Machinery; Automotive engineering; Robotics; Automation; Engineering; Machinery and Machine Elements; Robotics and Automation; Engineering Design; Automotive Engineering; Electronic books